ANALISIS PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK RITEL TERHADAP FREKUENSI BELANJA DI SURABAYA - NILAM, HERU (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Research objectives to be achieved are: to test and analyze the influence of shopping orientations on the shopping frequency, test and analyze the influence on the perceptions about the importance of retail attributes of shopping frequency, test and analyze the influence on the beliefs about retail attributes of shopping frequency. The benefits obtained research is to provide suggestion in an effort about consumer buying behavior effect the shopping frequency and as a reference for future research. The variables of the study include the independent variables and the dependent variable. Variable that are positioned as independent variable are: shopping orientation, perceptions of the importance of retail attributes, and beliefs about retail attributes. While the dependent variable is the shopping frequency, which are consists of shopping malls and strip center. Data analysis technique need is multiple linear regression. The findings in this study shows that in shopping orientation,only fashion orientation factor significantly affecting shopping frequency. In the variable of perceptions of the importance of retail attributes, only pleasure factor significantly affecting the shopping frequency. And the variable beliefs about retail attributes on shopping malls and strip centers significantly affecting shopping frequency. The nature of the influence of these variables are positive and negative, it means that when these factors increase then the shopping frequency is also increase, and vice versa.